Validation of cognitive inhibitors to technology adoption using content analysis. (17th December 2021) - Iyer, Easwar Krishna; Unnikrishnan, Sreehari; Philip, Paul; Sundarrajan, Mallika; Sivakumaran, Bharadhwaj
Inhibitors to technology play a crucial role in predicting eventual technology adoption. In the inhibitor space, studies have so far been limited to understanding affective inhibitors only. The central proposition of this paper is to identify two new cognitive inhibitor constructs. This study augments the existing body of knowledge in the area of technology acceptance behaviour by positing 'dissatisfiers' and 'risk' as two cognitive inhibitor constructs to technology adoption. The methodology used for validating the proposed model is content analysis (CA). The target technology chosen for validation is internet of things (IoT). The results obtained provide strong support for the proposed hypotheses thereby establishing dissatisfiers and risk as two new cognitive inhibitor constructs.